Embroidery Training as an Effort to Improve Economic Independence of the Elderly in Small and Medium Enterprises Named “OBAT HATI” - Emmidia Djonaedi; Yoga Putra Pratama; Rachmah Nanda Kartika; Endang Yuniatri; HB Rudi Kusumantoro; Khalyla Hafsa (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Computerized embroidery sewing is an innovation that's relatively easy to learn and produces embroidered objects on fabric quickly and in a marketable way. This machine is ideal for seniors who still want to be productive and increase their income in their later years without having to spend too much time and effort learning to use it. Consequently, a community of seniors around Kranggan, Bekasi, who were interested in computerized embroidery sewing training was chosen. Before the training, participants were given a questionnaire to assess their prior knowledge of computerized embroidery techniques on fabric. It turned out that almost all participants had never used such a machine. As a result, during the training, when they gained new knowledge about using the embroidery machine, they were very enthusiastic about practicing and even suggested having more training sessions in the future to enhance their skills in embroidering prayer cloths and bags